2020
DOI: 10.1007/s10792-020-01489-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of tear inflammatory molecules and clinical correlations in evaporative dry eye disease caused by meibomian gland dysfunction

Abstract: Purpose To compare the levels of inflammatory molecules in tear samples between patients with meibomian gland dysfunction (MGD)-related evaporative dry eye (EDE) and healthy subjects and to analyze the correlations between the levels of tear inflammatory molecules and ocular surface parameters. Methods A total of 30 MGD-related EDE patients (48 eyes) and ten healthy volunteers (15 eyes) were enrolled. Dry eye-related examinations and questionnaires were obtained from all participants. The levels of nine inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 42 publications
1
22
1
Order By: Relevance
“…The corneal tissues were then harvested and used in SEM analysis, hematoxylin and eosin staining, and real-time PCR to detect the inflammatory marker (interleukin [IL]-8) and matrix metallopeptidase-9 (MMP-9). 26 , 27 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The corneal tissues were then harvested and used in SEM analysis, hematoxylin and eosin staining, and real-time PCR to detect the inflammatory marker (interleukin [IL]-8) and matrix metallopeptidase-9 (MMP-9). 26 , 27 …”
Section: Resultsmentioning
confidence: 99%
“…However, on day 19, the RT-PCR result was negative for SARS-CoV-2. 26 In another report, one hospitalized patient had SARS-CoV-2-positive conjunctival swabs up to day 21 from symptom onset; however, after a few days, the virus was undetectable in nasal swabs. Five days later, the virus was undetectable in the conjunctival swab but was detected on day 27, suggesting sustained replication of the virus in the conjunctiva.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The conjunctival expression of matrix metalloproteinase 9 and transglutaminase 2 was shown to be higher in patients with Meibomian gland dysfunction and showed inflammation of epithelial damage due to impaired tear secretion [ 20 ]. Patients with Meibomian gland dysfunction-related DED also had higher levels of inflammatory molecules, such as IL-6, IL-8, IFN-γ and ICAM-1, in their tears compared to control subjects [ 21 ]. In a study conducted by Macri et al, patients with DED were also shown to have increased levels of oxidative stress by assessing lipid peroxidation with the LP-CHOLOX test [ 22 ].…”
Section: Dry Eye Diseasementioning
confidence: 99%
“… 2 Although it is recognized that inflammation is regarded as a key factor in the development of DED as well as the cause of ocular symptoms and signs, 3–5 the exact mechanism of inflammation in DED remains unclear. It has long been considered that ocular inflammatory markers could be related with the incidence of DED, 6 however, the relatively smallamount of tear samples and high detection cost have limited their clinical application in DED cases.…”
Section: Introductionmentioning
confidence: 99%